Single versus double drainage in chronic subdural hematomas treated with burr-holes - Ernesto Enrique Horta-Tamayo; Luis Cesar Acosta-Gonzalez; Diana Rosa Ortega-Raez; Lazaro Noel Parra-Vidal; Martha Suarez-Cruz (Revista Cubana de Medicina Militar)
Introduction: Chronic subdural hematoma is a frequent type of intracranial hemorrhage. Treatment for symptomatic cases is generally surgical. Burr-hole completion is the method of choice. Objective: To analyze the placement of a single versus double drain in patients with chronic subdural hematoma operated through burr-holes. Methods: An analytical correlational retrospective study was carried out in patients who underwent surgery for chronic subdural hematoma, between January 2018 and December 2020. The patients were divided into 2 groups based on the number of drains used: double or single. The variables were: age, morbidities, preoperative Glasgow Score, hematoma characteristics (laterality, internal architecture, maximum diameter, and midline shift), complications, and hospital stay. The probability value < 0.05 was considered statistically significant. Results: Of the 99 patients in the study, 39 were older than 75 years. The most frequent pattern was B with 25 cases (25,3 %). The diameter of the chronic subdural hematoma was more than 20 mm in 61 cases, and in 32 cases the displacement of the midline structures was greater than 10 mm. The average hospital stays 5,8 days. The most frequent complication was nosocomial pneumonia with eleven cases (11,11 %). The double drainage group showed fewer complications at 30 days. Conclusions: The placement of double subdural drainage in patients with chronic subdural hematoma operated through single or double burr-holes, and is related to fewer complications than those with single drainage.